2017
DOI: 10.1007/s00109-017-1556-y
|View full text |Cite
|
Sign up to set email alerts
|

4-O′-methylhonokiol protects from alcohol/carbon tetrachloride-induced liver injury in mice

Abstract: Methylhonokiol improves liver damage and survival. Methylhonokiol reduces hepatic fibrosis and necroinflammation. Methylhonokiol prevents myofibroblast activation and induces apoptosis. Methylhonokiol upregulates endocannabinoids and related N-acylethanolamines. Methylhonokiol contributes to lipid hydrolysis via PPARα/γ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Magnolol also attenuated ConA-induced liver fibrosis and suppressed human LX2 HSC activation, which was closely related to inhibiting Th17 cell differentiation by suppressing IL-17A generation [ 141 ]. In addition, other honokiol derivatives, such as 4′-O-methylhonokiol, also prevented from HSC activation and induced apoptosis via regulation of Bak1 and Bcl-2 expression [ 142 ].…”
Section: Lignansmentioning
confidence: 99%
“…Magnolol also attenuated ConA-induced liver fibrosis and suppressed human LX2 HSC activation, which was closely related to inhibiting Th17 cell differentiation by suppressing IL-17A generation [ 141 ]. In addition, other honokiol derivatives, such as 4′-O-methylhonokiol, also prevented from HSC activation and induced apoptosis via regulation of Bak1 and Bcl-2 expression [ 142 ].…”
Section: Lignansmentioning
confidence: 99%
“…In particular, the cannabinoid receptors CB1 and CB2 are upregulated in almost all chronic liver diseases, as well as cirrhosis and related disorders, and these receptors can be therapeutically antagonized[26-28]. Previous studies revealed that the CB2 agonists JWH-133 and 4′-O-methylhonokiol showed protective effects, such as decreased hepatocyte steatosis, inflammation, and liver regeneration[29-31]. In this study, we noted higher levels of CEA during the process of liver fibrosis, representing continuously increased concentrations of a CB2 agonist against CCl 4 -induced liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…In highfat diet-fed mice, MHK prevents fibrosis, organ injury, and lipid accumulation in liver, heart, and kidney [101,184,185]. Remarkably, MHK significantly downregulated CB 1 R overexpression and increased the hepatic concentrations of several N-acetylethanolamines, including AEA, OEA, and PEA [186].…”
Section: Cb 2 R-pparγmentioning
confidence: 96%